Liver‐specific knockout of GRP94 in mice disrupts cell adhesion, activates liver progenitor cells, and accelerates liver tumorigenesis. Issue 3 (27th January 2014) - Chen, Wan‐Ting; Tseng, Chun‐Chih; Pfaffenbach, Kyle; Kanel, Gary; Luo, Biquan; Stiles, Bangyan L.; Lee, Amy S.
<x xml:space="preserve">Abstract</x> Liver cancer is one of the most common solid tumors, with poor prognosis and high mortality. Mutation or deletion of the tumor suppressor phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is strongly correlated with human liver cancer. Glucose‐regulated protein 94 (GRP94) is a major endoplasmic reticulum (ER) chaperone protein, but its in vivo function is still emerging. To study the role of GRP94 in maintaining liver homeostasis and tumor development, we created two liver‐specific knockout mouse models with the deletion of Grp94 alone, or in combination with Pten, using the albumin‐cre system. We demonstrated that while deletion of GRP94 in the liver led to hyperproliferation of liver progenitor cells, deletion of both GRP94 and PTEN accelerated development of liver tumors, including both hepatocellular carcinoma (HCC) and cholangiocarcinoma (CC), suggestive of progenitor cell origin. Furthermore, at the premalignant stage we observed disturbance of cell adhesion proteins and minor liver injury. When GRP94 was deleted in PTEN‐null livers, ERK was selectively activated. Conclusion: GRP94 is a novel regulator of cell adhesion, liver homeostasis, and tumorigenesis. (Hepatology 2014;59:947–957)